Humiliation and Retaliation: Exploring Humiliation as One of the Main Causes of Global Terrorism in Pakistan - Dr. Syed Raza Shah Gilani; Muhammad Hamza Zakir (Social Science Review Archives, 2025)
Humiliation features in many forms in Pakistan’s fight against global terrorism, the Pakistani police use tools and methods that undermine the human dignity of their own citizens. The level of humiliation of people detained under Pakistan’s anti-terror laws has reached an unbearable limit, causing them to retaliate. Two factors shape the retaliation against anti-terror policing in Pakistan; one is the Pashtuns ‘strict adherence to their culture, while the other is the lack of police professionalism. The only shift in policing has been a negative one, consisting in increased violence and disrespect for human dignity.